Effect of Combinations of Quadriceps Exercise and Hip Abductor Exercise on Pain in Knee Osteoarthritis Patients in Orthopedic and Traumatology Outpatient Care - Dia Metasari; Tintin Sukartini; Arina Qona’ah (Indonesian Journal of Medicine, 2023)
Background: Osteoarthritis is a disorder of the moving joints. Pain functioning are the main complaints of the disease osteoarthritis of the knee. The purpose of the study was to analyze the effect of a combination of quadricep exercise and hip abductor exercise on pain in knee among osteoarthritis patients.Subjects and Method: The study was carried out at the East Java Regional Hospital for the period of December 2022 to March 2023. The study population was knee joint osteoarthritis patients of degree 1 to degree 2. The sampling technique used in this study was purposive sampling, with inclusion and exclusion criteria. The number of samples in quantitative research was 60 respondents. The dependent variable is pain, while the independent variable is quadriceps exercise and hip abductor exercise. The instrument used is the WOMAC questionnaire. Analysis of the study was using the Wilcoxon test and the Mann Whitney test.Results: There was a significant difference in pain between the control and intervention groups after conducting a combination of quadriceps exercises and hip abductor exercises (p=0.043)Conclusion: The combination of quadriceps exercise and hip abductor exercise is effective on pain reduction in knee osteoarthritis patients.Keywords: quadriceps, hip abductor, osteoarthritis.Correspondence: Dia Metasari. Master of Nursing, Universitas Airlangga, Indonesia. Jl. Dr. Ir. H. Soekarno, Mulyorejo, Surabaya, East Java 60115. Email: dia.metasari-2021@fkp.unair.ac.id. Mobile: +628563040303.Indonesian Journal of Medicine (2023), 08(02): 186-193https://doi.org/10.26911/theijmed.2023.08.02.08